Impacts assessment of municipal solid squander dumping in riparian corridor using multivariate statistical techniques - Singh A.N.; Gautam D.K.; Kumar P.; Mohan D. (My University, 2025)
Crumbling soil quality and reduction in vegetation plenitude are grave outcomes of open squanders dumping which have brought about growing public concern. The center of the present study is to assess the contribution of open squander dumping in riparian soil contamination and its impact on plant assorted qualities in riparian corridor of river Varuna. Surface soil sample (n = 6 + 2) was gathered from both the open squander dumping and control site. The assorted qualities of vegetation were learned at both sites. Significant changes were seen in the soil attributes of the dumping sites. Soils at the dumping indicated high pH, TDS and EC regime in contrast with control site. The assorted qualities of vegetation were also learned at both sites. A comparable pattern was seen in plant assorted qualities. Control site indicated differentiated assortment of plants, i.e., 12 plant species while this number decreased at the dumping sites. The principal component analysis created three significant components explaining 95.764 of the variance in the data attributable to open dumping effect. Hierarchical cluster analysis grouped six-dumping sites into three clusters having similar characteristics and source of contamination, i.e., moderate and highly polluted dumping sites. © Springer Nature Singapore Pte Ltd. 2017. All rights reserved.